I'm trying to simplify the following, using the basic pythagorean identities or other basic trig: (cos^3 θ + sin^3 θ )/(sin θ + cos θ ) Any help would be appreciated.
Follow Math Help Forum on Facebook and Google+
(cos^3 θ + sin^3 θ )/(sin θ + cos θ )= =(cos θ + sin θ )*(cos^2 θ - sin θ cos θ + sin^2 θ) / (sin θ + cos θ ) = =cos^2 θ - sin θ cos θ + sin^2 θ = 1-sinθ cos θ =1-(1/2) sin2θ
Nice! Thank you. So did you factor (cos θ + sin θ) out of the denominator? How did you go about doing that?
Last edited by breadmaker; November 21st 2008 at 02:08 PM.
a^3+b^3=(a+b)(a^2-ab+b^2)
View Tag Cloud